Design Thinking Approach in Designing “Care-Pet” Crowdfunding Platform for Abandoned Cats and Dogs in Indonesia - Ani Nuraisyah; Fuad Wahdan Muhibuddin; Asep Taryana; Suhendi (School of Business, IPB University (SB-IPB), 2022)
Abandoned cats and dogs have the right to a decent life. In Indonesia, there are still many abandoned cats and dogs with various conditions that are not good. This research aims to design the right crowdfunding platform that can answer community problems in improving animal welfare. Respondents in this study were pet lovers (cat/dog lovers). Data is obtained by filling out questionnaires in in-depth interviews. The method used in this study is design thinking. This method can solve user-centered problems. The design thinking stages include empathize, define, ideate, prototype, and test. The results showed that crowdfunding is one solution to solve the problems and challenges faced by the community in caring for abandoned cats/dogs. The design of a verified business model in the form of a crowdfunding platform for abandoned cats and dogs named Care-pet is a solution that can improve animal welfare. Keywords: business model, crowdfunding, design thinking, pet lovers, prototype